Analysis of Healthy Lifestyles According to Digital Health Literacy in Adolescent Girls Aged 11-19 Years - Irfan Nafis Sjamsuddin; Tuti Surtimanah (Health Science UDINUS, 2023)
Adolescent health problems are generally related to risky behavior and lifestyle. Adolescents' healthy lifestyles are influenced by various factors. one of which is health literacy. Teenagers tend to use new media as a source of information. so a different health literacy approach is needed namely digital health literacy. The research aims to determine the relationship between digital health literacy and a healthy lifestyle in adolescent girls aged 11-19 years. A research method is a descriptive analysis that uses secondary data. The population was 689 adolescent girl women aged 11-19 years. with a sample of 530 people selected purposively. The secondary data used was collected through interviews and anthropometric measurements. The data analysis is univariate and bivariate. The results showed that adolescent girls had good eating habits were 59.7%; 53.2% had good physical activity but 69.4% had smoked. Digital health literacy was 54.5% in the high category. and the literacy components of accessing information. evaluating. and applying information were mostly in the high category. The conclusion is there’s no relationship (p > 0.05) between digital health literacy and eating behavior. physical activity. and smoking behavior. However. there is a relationship (p<0.05) between the information access component and smoking behavior. It is necessary to study qualitatively related to this study.